Strategies and Dynamics of Online Fraud in Indonesia: Tracing the Effectiveness of the Implementation of the Electronic and Transaction Information Act - Muh. Akbar Fhad Syahril; Ardiyanti Aris (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
This study explores the implementation of the Electronic Information and Transaction Law (UU ITE) in handling online fraud cases in Indonesia, using normative-empirical legal methods. Although the UU ITE provides a comprehensive legal framework, its effectiveness is hampered by challenges in proving and tracing perpetrators, limited resources and technology in law enforcement agencies, and the complexity of cross-border cases. The data shows a significant increase in online fraud cases from 115,756 reports in 2021 to 130,000 victims in 2022. This research highlights the importance of a holistic approach that includes improving regulations, increasing the capacity of law enforcement, strengthening international cooperation, and increasing people's digital literacy. In addition, the development of artificial intelligence (AI) technology and a multi-stakeholder approach were identified as important strategies in the prevention and early detection of online fraud. Recommendations, including the revision of the UU ITE to accommodate technological developments and harmonization with the Criminal Code, are expected to improve the success of handling online fraud cases and create a safer digital environment in Indonesia.